Exceptional carbon uptake in European forests during the warm spring of 2007: a data–model analysis - DELPIERRE, N.; SOUDANI, K.; François, C.; Köstner, B.; Pontailler, J.-Y.; NIKINMAA, E.; Misson, L.; Aubinet, M.; BERNHOFER, C.; GRANIER, a; GRÜNWALD, T.; HEINESCH, B.; et al. (Global Change Biology, 2009)
Temperate and boreal forests undergo drastic functional changes in the springtime, shifting within a few weeks from net carbon (C) sources to net C sinks. Most of these changes are mediated by temperature. The autumn 2006–winter 2007 record warm period was followed by an exceptionally warm spring in Europe, making spring 2007 a good candidate for advances in the onset of the photosynthetically active period. An analysis of a decade of eddy covariance data from six European forests stands, which encompass a wide range of functional types (broadleaf evergreen, broadleaf deciduous, needleleaf evergreen) and a wide latitudinal band (from 44° to 62°N), revealed exceptional fluxes during spring 2007. Gross primary productivity (GPP) of spring 2007 was the maximum recorded in the decade examined for all sites but a Mediterranean evergreen forest (with a +40 to +130 gC m−2 anomaly compared with the decadal mean over the January–May period). Total ecosystem respiration (TER) was also promoted during spring 2007, though less anomalous than GPP (with a +17 to +93 gC m−2 anomaly over 5 months), leading to higher net uptake than the long-term mean at all sites (+12 to +79 gC m−2 anomaly over 5 months). A correlative analysis relating springtime C fluxes to simple phenological indices suggested spring C uptake and temperatures to be related. The CASTANEA process-based model was used to disentangle the seasonality of climatic drivers (incoming radiation, air and soil temperatures) and biological drivers (canopy dynamics, thermal acclimation of photosynthesis to low temperatures) on spring C fluxes along the latitudinal gradient. A sensitivity analysis of model simulations evidenced the roles of (i) an exceptional early budburst combined with elevated air temperature in deciduous sites, and (ii) an early relief of winter thermal acclimation in coniferous sites for the promotion of 2007 spring assimilation.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 13 october 2008; august 2008 and accepted; European forests; functional drivers; net carbon uptake; process-based model; received 30 may 2008; revised version received 30; spring